Oral contraceptives do not impact metabolic and cardiorespiratory response during acute high-intensity rowing interval exercise — a pilot study - Garcia, Sara; Olenick, Alyssa; Jenkins, Nathan; Pearson, Regis (Health Promotion & Physical Activity, 2025)
Purpose: Increasing prevalence of oral contraceptive (OC) use in physically active females highlights the need for sex-specific exercise metabolism research. This pilot study investigated the influence of chronic OC use on the exercising metabolic and respiratory response during a rowing high-intensity interval exercise (HIIE) protocol in young, healthy, moderately active females. Methods: Fifteen females [21.9 (3.7) years] were categorized by OC (n = 6) vs. non-oral contraceptive use (NOC) (n = 9). HIIE was four sets of 3 min maximal effort intervals on the rowing ergometer with 3 min rest between intervals and performed during the follicular phase (days 2–10 or inactive pills) of participants’ menstrual cycles. To confirm comparable physical profiles of participants, we collected body fat percentage, fat-free mass, bone mineral density, blood pressure, aerobic fitness, muscular strength and endurance, flexibility, and microvascular function. Results: Groups were similar in all measures of physical profiles (P > 0.05). Our pilot study showed that OC use or NOC use did not influence the exercising metabolic and cardiorespiratory response to HIIE in young, healthy, moderately active females. Fat oxidation, carbohydrate oxidation, metabolic flexibility, blood lactate concentration, blood glucose, and cardiorespiratory response were similar between groups (P > 0.05). Conclusion: These findings suggest that there was no significant difference in exercising metabolic and cardiorespiratory response between OC and NOC users.